What Drives Volunteers to Accept a Digital Platform That Supports NGO Projects? - Saura, Jose Ramon; Palos-Sanchez, Pedro; Velicia-Martin, Felix (Frontiers in Psychology, 2020)
Technology has become the driving force for both economic and social change. However, the recruitment of volunteers into the projects of non-profit making organizations (NGOs) does not usually make much use of Information and Communication Technology (ICT). Organizations in this sector should incorporate and use digital platforms in order to attract the most well-prepared and motivated young volunteers. The main aim of this paper is to use an extended Technology Acceptance Model (TAM) to analyze the acceptance of a technological platform that provides a point of contact for non-profit making organizations and potential volunteers. The TAM model is used to find the impact that this new recruitment tool for volunteers can have on an ever-evolving industry. The TAM model has been extended with the Image and Reputation and Visual Identity variables in order to measure the influence of these non-profit making organizations on the establishment and implementation of a social network recruitment platform. The data analyzed is from a sample of potential volunteers from non-profit making organizations in Spain. A structural equation approach using partial least squares was used to evaluate the acceptance model. The results provide an important contribution to the literature about communication in digital environments by non-profit making organizations as well as strategies to improve their digital reputation.